General psychosocial measures are affected by the situation preceding assessment: The ‘arbitrary distinction’ between state and trait measures is still unresolved - Szabo, Attila; Ábel, Krisztina (Psichologija, 2021)
General psychosocial measures are assumed to be stable over time. However, such measures may be affected by the situation preceding assessment. In this study 28 participants completed the WHO-5 Well-Being Index, the Subjective Happiness Scale, and the Life Orientation Test which are general measures, and the Positive Affect Negative Affect Schedule and the Feeling Scale which are state measures. Subsequently, the first part of ‘Mega Disasters Nagasaki The Forgotten Bomb’ documentary was presented to the participants. Following the intervention, they completed the same measures again. State measures of negative affect increased, feeling state decreased as expected, but retrospectively measured well-being as well as the index of optimism also decreased. There were large individual differences. The findings indicate that general measures, assumed to be stable over time, are influenced by the situation. Therefore, there is a need for reporting, as well as controlling, the events preceding their measurement. The implication of these findings is that hundreds of empirical results based on general or trait measures may be invalid if any event preceding their assessment had an emotional impact.
Keywords: assessment; questionnaire; scale; state; trait